Optimalisasi Penerapan Kebijakan QRIS Sebagai Alat Pembayaran NonTunai pada UMKM Kuliner di Pasar Lama Kota Tangerang - Yusuf, Maulana; Cadith, Juliannes (Laboratorium Jurusan Ilmu Administrasi Negara Fakultas Ilmu Sosial Universitas Negeri Padang, 2024)
The aim of this research is that the researcher refers to 2 discussions, namely measuring effectiveness and strategy in optimizing QRIS policies, especially in Old Market, Tangerang City. The research method used in this research is a quantitative approach. The data analysis techniques used are 2 types, namely quantitative effectiveness and SWOT data analysis techniques. The Data Analysis Techniques for Measuring Effectiveness include Validity Test, Reliability Test, Normality Test, T Test, and Hypothesis Test. Meanwhile, the SWOT Data Analysis Test is IFAS and EFAS which are the characteristics of SWOT Data Analysis itself. The results of the research show that the effectiveness of the QRIS policy is effectiveness with an overall percentage gain of 71%, while data analysis calculations are used by researchers to optimize the QRIS policy in Pasar Lama Tangerang City, where the optimization is in the form of providing alternative strategies that can be used in optimizing the policy QRIS itself. Providing alternative strategies can be applied as recommendations from researchers to agencies related to QRIS or the Tangerang City Government which have been adjusted to the needs of implementing QRIS policies, so that this research not only assesses or measures in terms of effectiveness but can also provide alternative strategies from researchers to readers. . This research suggestion is intended as information for campus institutions, service institutions and readers as a strategic reference that can be used to strengthen the QRIS policy itself in Old Market Tangerang City.